ANALISIS KESTABILAN EMOSI SISWA KELAS X SMA N 1 BENAI TAHUN AJARAN 2015/2016 - Warianto, Wisnu Warianto Wisnu; Umari, Tri Umari Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Teenagers is individuals figure that in the process of changing from childhood to adulthood. To many high school teens can’t be controling their emotions, is evident from their behavior at school. Various things that be reflection the emotional instability occurs students at high school. The intend for this survey is 1) To knowing the emotional stability student class X SMAN 1 Benai Academic Year 2015/2016, 2) To analyze the emotional stability by item class X SMAN 1 Benai the Academic Year 2015/2016. The instrument to be using at this survey is emotional stability scale of students, compiled by Marleni, 2013 as 50 items that was been testing on the validity and reliability with results is Valid and Reliable. Subjects in this survey were students of class X 1, X 2, X 3, X 4, SMAN 1 Benai academic year 2015/2016, amounted to 126 people. Sampling undertaken by the author is using the technique of total sampling (full sample) that all population be used as members of the sample. The results showed found as 21 students (16.67%), who have a very high emotional stability, 70 students (55.56%) who have a high emotional stability, 23 students (18.25%) who have a medium emotional stability and 12 students (9.52%) who had low emotional stability.Key Words: Emotional Stability